Rural Youth Entrepreneurial Aspiration: An Assessment Of Tpb And Self-efficacy - Nor Irwani Abdul Rahman; Amalina Mursidi; Suhaida Herni Suffarruddin; Nur Rasyidah Aida Hazwani Rusdi (UUM Press, 2024)
Indexed by MyCite